PURITANISM OF ISLAM IN ISLAMIC BOARDING SCHOOL (PESANTREN) (Models of Religious Understanding in Puritan Pesantren in East Java) - M. Arfan Mu'ammar (Reflektika, 2017)
Religious purification in Indonesia is often considered as radical movement of Islam, the straitlaced and extreme one. This research aimed to explore religious understanding of the puritans. Six of pesantren were selected as those are considered as the proper representative of those puritan pesantren. Qualitative descriptive method was employed to analyze the data. The result showed that those six pesantren are varied in the quality of how puritan they are. Those pesantren can be grouped into three groups, radical, accomodationists, and moderinists. The grouping is based on how they deal with the concert issues occurring in the society. The radicals tend to strait-lacedly deal those issues. The accomodationists are more flexible than the radicals as they prohibit some issues under certain condition and purpose. On the contrary, the modernists are more lenient with the tajdid issues.    Religious purification in Indonesia is often considered as radical movement of Islam, the straitlaced and extreme one. This research aimed to explore religious understanding of the puritans. Six of pesantren were selected as those are considered as the proper representative of those puritan pesantren. Qualitative descriptive method was employed to analyze the data. The result showed that those six pesantren are varied in the quality of how puritan they are. Those pesantren can be grouped into three groups, radical, accomodationists, and moderinists. The grouping is based on how they deal with the concert issues occurring in the society. The radicals tend to strait-lacedly deal those issues. The accomodationists are more flexible than the radicals as they prohibit some issues under certain condition and purpose. On the contrary, the modernists are more lenient with the tajdid issues.